Mapping the Discursive Barriers of Religious Moderation in Islamic Schools: A Systematic Literature Review of Sinta-Indexed Research (2019–2026) - Bambang Supradi; Ali Muddin Jailani; Mustafa Mustafa; Syahrur Ramli; M Yoga Habibullah; Yudha Putra Pratama; Radhitiya Dwi Putra (Yayasan Darussalam Bengkulu, 2025)
This systematic literature review investigates the structural and discursive barriers hindering the implementation of state-led religious moderation policies in Indonesian Islamic schools (Madrasahs). Utilizing the PRISMA framework to analyze 35 selected articles from Sinta-indexed journals published between 2019 and 2026, the study maps the implementation bottlenecks into three primary problem clusters: ideological-epistemological resistance, pedagogical-curricular constraints, and institutional policy ambiguities. The findings reveal a profound structural paradox: rather than fostering genuine civic tolerance, the top-down imposition of standardized moderation modules inadvertently triggers a defensive theological response from frontline educators. Driven by fears of 'theological dilution' (pendangkalan akidah) and burdened by rigid administrative compliance metrics, schools frequently resort to institutional decoupling—displaying superficial symbols of compliance while maintaining traditional, exclusionary classroom dynamics. Furthermore, a resource-driven divide exacerbates systemic inequalities between wealthy urban institutions and underfunded rural schools, forcing the latter to rely on informal, localized religious networks that fracture national standardization. This review argues that the current securitized, state-imposed approach destroys pedagogical trust and alienates educators. To overcome this impasse, policymakers must transition from punitive bureaucratic mandates toward a collaborative governance model that re-centers educational autonomy and utilizes traditional Islamic frameworks like wasathiyah.